Pengaruh Jumlah Anak, Pengetahuan dan Sikap dengan Pemilihan Metode Kontrasepsi Jangka Panjang pada AkseptorKB di Kota Pekanbaru - Ranti Puspa Lestari; Bambang Setiaji; Emy Leonita; Nurlisis Nurlisis; Juli Selvi Yenti (STIKes Hang Tuah Pekanbaru, 2022)
Family planning (KB) is an effort to control the number and distance between births. MKJP (Long-term Contraception Method) is a contraceptive that can last between three years to a lifetime, such as IUDs, implants, and sterilization for men/women. The research objective was to determine the factors associated with the choice of long-term contraceptive methods for family planning acceptors in Pekanbaru City, such as age, the number of children, knowledge, attitudes, support from husbands, and support from health workers. This study used a quantitative research method with a cross-sectional analytic research design and this research was augmented by doing simple qualitative research in which researchers did a deep interview. This research was done from July to August of 2020. This study used univariate, bivariate, and multivariate analysis. There were 60 respondents of this study from all KB acceptors in Pekanbaru. The results showed that the p-value <0.05 was among other variables the number of children (p = 0.002) with POR = 11.047, the knowledge variable (p = 0.036) with POR = 4.586 strengthened by qualitative research: